Ponadzaborowy charakter krakowskich obchodów trzechsetlecia śmierci Piotra Skargi - Cabaj, Jarosław (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2013)
On 25–27th September 1912, scientific and clergy circles in Cracow hosted the Catholic Congress to commemorate Piotr Skarga. It constituted the main element of the Polish commemoration of the 300th Anniversary of Piotr Skarga’s death. Beyond-partitions nature of the meeting was reflected in the composition of the organizing committee, the issues discussed, and the resolutions passed. The Congress also provided an opportunity to manifest the connections between Polish circles in public.The Congress’ commemoration of Piotr Skarga should also be considered as an element of a reliable method that allowed scientific and socio-professional circles to establish and maintain contacts beyond partitions.